Functional analysis of H. sapiens DNA polymerase γ spacer mutation W748S with and without common variant E1143G - Palin, Eino JH (2010)
Mitochondrial DNA polymerase, POLG, is the sole DNA polymerase found in animal mitochondria. In humans, POLGα W748S in cis with an E1143G mutation has been linked to a new type of recessive ataxia, MIRAS, which is the most common inherited ataxia in Finland. We investigated the biochemical phenotypes of the W748S amino acid change, using recombinant human POLG. We measured processive and non-processive DNA polymerase activity, DNA binding affinity, enzyme processivity, and subunit interaction with recombinant POLGβ. In addition, we studied the effects of the W748S and E1143G mutations in primary human cell cultures using retroviral transduction. Here, we examined cell viability, mitochondrial DNA copy number, and products of mitochondrial translation. Our results indicate that the W748S mutant POLGα does not exhibit a clear biochemical phenotype, making it indistinguishable from wild type POLGα and as such, fail to replicate previously published results. Furthermore, results from the cell models were concurrent with the findings from patients, and support our biochemical findings.